INTERFERENCE BETWEEN VIABLE STRAINS OF NEWCASTLE DISEASE VIRUS - Durand, D. P. (1961)
Durand, D. P. (University of Missouri, Columbia). Interference between viable strains of Newcastle disease virus. J. Bacteriol. 82:979–983. 1961.—Strains of Newcastle disease virus (NDV) which differed in their ability to produce plaques on monolayers of chicken embryo cells were studied during conditions of dual infection. Interference with NDV plaque formation by a nonplaque-forming NDV strain was observed. The primary mechanism involved with this type of interference appears to be due to the viable infectious virus, and is not associated with interferon production or the hemagglutinin of NDV.